2004
DOI: 10.1037/0021-9010.89.1.36
|View full text |Cite
|
Sign up to set email alerts
|

The Forgotten Ones? The Validity of Consideration and Initiating Structure in Leadership Research.

Abstract: This study provided a meta-analysis of the relationship of the Ohio State leadership behaviors--Consideration and Initiating Structure--with leadership. Overall, 163 independent correlations for Consideration and 159 correlations for Initiating Structure were analyzed. Results revealed that both Consideration (.48) and Initiating Structure (.29) have moderately strong, nonzero relations with leadership outcomes. Consideration was more strongly related to follower satisfaction (leader satisfaction, job satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

66
927
7
33

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 986 publications
(1,033 citation statements)
references
References 141 publications
66
927
7
33
Order By: Relevance
“…Consideration is defined as the degree to which a supervisor shows concern and respect for his or her workers, looks out for their well-being, and expresses support and appreciation [30]. The LBDQ has the highest validity for measuring consideration and structure compared to three other leadership questionnaires (Cronbach's α equal to 0.81) [31]. The LBDQ scores range from 0 to 60 on each of the two dimensions of leadership.…”
Section: Primary Study Measuresmentioning
confidence: 99%
“…Consideration is defined as the degree to which a supervisor shows concern and respect for his or her workers, looks out for their well-being, and expresses support and appreciation [30]. The LBDQ has the highest validity for measuring consideration and structure compared to three other leadership questionnaires (Cronbach's α equal to 0.81) [31]. The LBDQ scores range from 0 to 60 on each of the two dimensions of leadership.…”
Section: Primary Study Measuresmentioning
confidence: 99%
“…There is lack of evidence from previous research about the 10 relationship between task-focused leadership and team learning. Findings do, however, demonstrate a moderate influence of task-focused leadership on team performance (r = .23) (Judge et al, 2004). This suggests employing a research design that takes into account task-focused leadership behavior as a possible factor to explain team learning behaviors.…”
mentioning
confidence: 92%
“…We follow the first stream and adhere to Edmondson (1999), who defined team learning as an ongoing process of collective reflection and action. Savelsbergh, Van der Heijden, and Poell (2009) characterized this process by eight team learning behaviors: (1) exploring; (2) coconstruction of meaning, (3) reflecting on outcomes and (4) processes; (5) communicating; (6) discussing errors and unexpected outcomes of actions; (7) seeking feedback; and (8) (Burke et al, 2006;Judge, Piccolo, & Ilies, 2004;Stogdill, 1950), which will be elaborated upon below.…”
Section: Learning In Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Social psychological and social justice research has shown that interpersonal respect can generate pro-social behaviour such as fulfilling one's roles as a member of a group (van Quaquebeke et al 2009;Simon and Sturmer 2003;Tyler and Blader 2000). Organisational research has shown that respectful leadership can enhance motivation, job satisfaction, and performance (Judge et al 2004). In contrast, individuals and groups who perceive themselves to be unfairly disrespected tend to feel anger and a sense of injustice (Miller 2001).…”
Section: The Effects Of Perceived Disrespectmentioning
confidence: 99%